Nursing Care for Mrs. W Diagnosed with Hypertensive Urgency using Foot Massage Therapy in the Emergency Department - Najihah, Umi; Ekawati, Indi; Budiati, Dian; Yulianingsih, Yulianingsih; Karlina, Nonok (Al Makki Health Informatics Journal, 2024)
Hypertensive emergency is a hypertensive crisis characterized by a sudden increase in blood pressure of 180/110 mmHg without organ damage. Hypertensive disease has increased every year due to low awareness of compliance in taking medication and maintaining a healthy lifestyle in hypertensive patients. The purpose of this case study is to provide nursing care to patients experiencing hypertension urgency. This research method uses a qualitative approach with case studies as the main method, using observation sheets, interviews, and documentation studies. This case study chose one patient as the research subject, namely a patient with hypertensive urgency in the emergency room of Gunung Jati Hospital, Cirebon City. Nursing care management is based on meeting the needs of patients carried out in 1 day. The results of the case study showed that after being given nursing care there was a decrease in blood pressure from 195/110 mmHg to 187/104 mmHg. The conclusion is that the nursing care provided is effective in emergency hypertension patients and meets the needs of patients. The implication of this study is the importance of nursing care in managing hypertension emergencies, which can help in the effective monitoring and management of this disease. In addition, this study also strengthens the understanding of the importance of patient compliance in managing hypertension to prevent complications that can arise.